2019
DOI: 10.1155/2019/4903152
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as Potential Biomarkers for Chemoresistance in Adenocarcinomas of the Esophagogastric Junction

Abstract: Concerning adenocarcinomas of the esophagogastric junction, neoadjuvant chemotherapy is regularly implemented, but patients’ response varies greatly, with some cases showing no therapeutic effect, being deemed as chemoresistant. Small, noncoding RNAs (miRNAs) have evolved as key players in biological processes, including malignant diseases, often promoting tumor growth and expansion. In addition, specific miRNAs have been implicated in the development of chemoresistance through evasion of apoptosis, cell cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 88 publications
(106 reference statements)
0
10
0
Order By: Relevance
“…While changes in death receptor expression were insignificant at a transcriptional level, studies have demonstrated that chemoresistance can alter receptor abundance via mechanisms of translational regulation ( Si et al, 2019 ; Just et al, 2019 ). Confocal microscopy showed that oxaliplatin-resistant cells have increased DR4 in both HCT116 ( Figure 3A ) and SW620 ( Figure 3B ) cell lines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While changes in death receptor expression were insignificant at a transcriptional level, studies have demonstrated that chemoresistance can alter receptor abundance via mechanisms of translational regulation ( Si et al, 2019 ; Just et al, 2019 ). Confocal microscopy showed that oxaliplatin-resistant cells have increased DR4 in both HCT116 ( Figure 3A ) and SW620 ( Figure 3B ) cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, DR4 augmentation appears to be independent from transcriptional upregulation as there was no significant change in mRNA expression between OxR and parental cell lines. Increasing evidence demonstrates that chemoresistance affects small non-coding microRNA (miRNA) expression, which modulates transcriptional and translational processes ( Si et al, 2019 ; Just et al, 2019 ). More specifically, studies have shown that oxaliplatin treatment and subsequent resistance in CRC cells alter miRNA expression, affecting signaling pathways within p53, epithelial-to-mesenchymal transition, and cell migration ( Tanaka et al, 2015 ; Gasiulė et al, 2019 ; Evert et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…While changes in death receptor expression were insignificant at a transcriptional level, studies have demonstrated that chemoresistance can alter receptor abundance via mechanisms of translational regulation (30,31). Confocal microscopy showed that oxaliplatin-resistant cells have increased DR4 in both HCT116 ( Fig 3A ) and SW620 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The role of let-7f-5p acted as biomarker was also explored. A previous study revealed that let-7f-5p was a prognostic biomarker for chemoresistance in adenocarcinomas of the esophagogastric junction [30]. In addition, Marcia et al found that let-7f-5p combined with other four miRNAs showed high diagnostic accuracy for Parkinson's disease [31].…”
Section: Discussionmentioning
confidence: 99%